THE INFLUENCE OF GREEN MARKETING AND BRAND IMAGE ON PURCHASING DECISIONS FOR EMINA NATURAL PAL SERIES PRODUCTS IN SAMARINDA (Study on consumers of Emina Natural Pal Series products in Samarinda) - Setya Fachtia Rusman Z.A RUSMAN AK; Mukhibatul Hikmah; Lailatul Hijrah; Poppy Alvianolita Sanistasya (Faculty of Social and Political Sciences, Universitas Lampung, 2025)
Consumer desire for cosmetics is growing the fastest. With more and more environmental damage problems, Emina has released the Natura Pal Series, a line of cosmetics that are safe for the environment. This study wants to find out if green marketing and the way a brand is seen in Samarinda affect people's decisions to buy Emina Natural Pal Series products. Respondents to this study were given surveys as part of a quantitative way to collect data. One hundred women from Samarindabetween the ages of 17 and 25 who had bought EminaNatural Pal Series goods took part in this study. A quantitative study method was used, and data were gathered through polls. The study group was made up of Emina users in Samarinda. They were chosen through a method called